2007
DOI: 10.1016/j.ydbio.2007.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Functional BMP receptor in endocardial cells is required in atrioventricular cushion mesenchymal cell formation in chick

Abstract: Transformation of atrioventricular (AV) canal endocardium into invasive mesenchyme correlates spatially and temporally with the expression of bone morphogenetic protein (BMP)-2 in the AV myocardium. We revealed the presence of mRNA of Type I BMP receptors, BMPR-1A (ALK3), BMPR-1B (ALK6) and ALK2 in chick AV endocardium at stage-14(-), the onset of epithelial to mesenchymal transformation (EMT), by RT-PCR and localized BMPR-1B mRNA in the endocardium by in situ hybridization. To circumvent the functional redund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 62 publications
2
30
2
Order By: Relevance
“…8,16 The development of this isolating structure involves several processes in which the endocardial cushions that line the luminal side of the primitive AV canal, together with the inward migration of the epicardially located AV sulcus tissue, play an important role. [17][18][19] Recently, it has been shown in more detail that a combination of bone morphogenetic protein signaling, 20,21 periostin (an osteoblast-specific factor), 22 and epicardiumderived cells that enter the heart at the AV sulcus play a key role in this process. 23,24 The cause of APs has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…8,16 The development of this isolating structure involves several processes in which the endocardial cushions that line the luminal side of the primitive AV canal, together with the inward migration of the epicardially located AV sulcus tissue, play an important role. [17][18][19] Recently, it has been shown in more detail that a combination of bone morphogenetic protein signaling, 20,21 periostin (an osteoblast-specific factor), 22 and epicardiumderived cells that enter the heart at the AV sulcus play a key role in this process. 23,24 The cause of APs has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of the BMP type 1A receptor in the endocardium also resulted in failed cushion formation, indicating that BMP signals directly to cushion-forming endocardium to induce epithelial-mesenchyme transition (27). Transformation of atrioventricular (AV) canal endocardium into invasive mesenchyme correlates spatially and temporally with the expression of BMPs in the atrioventricular myocardium crucial for the induction of Postn (28). Kühn et al (29) showed that periostin-induced cardiomyocyte cell-cycle reentry and mitosis, whereas periostin expression was associated with improved ventricular remodeling and myocardial function (30).…”
Section: Srf Orchestrates Cardiac Myogenesis Through Multiple Levels Ofmentioning
confidence: 99%
“…Both are critical to a variety of developmental processes including EMT aspects of morphogenesis (Chen et al 2004). BMP4 drives early mesoderm formation (Winnier et al 1995) while BMP2 is required for EMT during heart morphogenesis (Okagawa et al 2007). Homozygous deletions of BMP2 and BMP4 in mice are embryonic lethal due to abnormal heart development and a failure of mesoderm formation, respectively (Winnier et al 1995;Zhang and Evans 1996).…”
Section: Bmp4 Induces An Epithelial -Mesenchymal Transition-like Respmentioning
confidence: 99%